Dampak Strategi Investasi Nikel Indonesia terhadap Pertumbuhan Ekonomi di Dalam Negeri - Botutihe, Alya Nurhaliza; Kusuma Paksi, Arie (ILTIZAM Journal of Shariah Economics Research, 2024)
The aim of this study is to analyze the impact of Indonesia's nickel investment strategy, particularly in relation to the downstream policy implemented in 2020, on domestic economic growth. The research will examine in depth how the nickel downstreaming policy affects various aspects of the domestic economy, such as foreign direct investment (FDI), and how this increased investment can improve domestic economic transformation, nickel export value, as well as job creation. This research is studied using qualitative methods with descriptive research type by using library research techniques in data collection. The theory used in this research is the theory of protectionism which is defined as an effort to protect domestic businesses and government policies to control exports or imports through trade barriers, such as tariffs and quotas, in order to protect domestic industries from foreign competition. In this study, it was found that the nickel downstreaming and investment strategy had a positive impact on increasing investment figures, economic transformation, increasing export values, as well as an increase in job creation.